Risk Factors For Pre Eclampsia Incidents At Negara Regional Hospital: Secondary Data In 2022 - Sandy, Putu Wahyu Sri J; Pratama, Aditha Angga (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
The highest maternal mortality is currently caused by preeclampsia and eclampsia. Hypertension in pregnancy accompanied by edema and urine protein are early symptoms of preeclampsia. The purpose of this study was to analyze the risk factors for preeclampsia in RSUD Negara. This research method is quantitative with a restrospective cohort approach. Independent variables are risk factors including age, education, occupation, parity, history of hypertension, history of gemelli. The dependent variable is preeclampsia. The sampling technique in this study was total sampling with a sample size of 1,136 respondents. This study used secondary data by taking through patient medical records at the State Hospital from the beginning of 2022-end 2022. The analysis used univariate and bivariate analysis using chisquare. The results reported that the risk factors for preeclampsia were caused by low education (<0.0001), and a history of hypertension (<0.0001). It was concluded that there were 2 risk factors that significantly increased the incidence of preeclampsia.